Childhood and child labour in the British Industrial Revolution - Humphries, Jane, 1948- (Cambridge, UK ; New York : Cambridge University Press, 2014)
"This is a unique account of working-class childhood during the British industrial revolution. Using more than 600 autobiographies written by working men of the eighteenth and nineteenth centuries Jane Humphries illuminates working-class childhood in contexts untouched by conventional sources and facilitates estimates of age at starting work, social mobility, the extent of apprenticeship, and the duration of schooling. The classic era of industrialization, 1790-1850, apparently saw an upsurge in child labour. While the memoirs implicate mechanization and the division of labour in this increase, they also show that fatherlessness and large sibsets, common in these turbulent, high-mortality, and high-fertility times, often cast children as partners and supports for mothers struggling to hold families together. The book offers unprecedented insights into child labour, family life, careers, and schooling. Its images of suffering, stoicism, and occasional childish pleasures put the humanity back into economic history and the trauma back into the industrial revolution"--
Machine generated contents note: 1. Introduction; 2. Sources, models, context; 3. Families; 4. Household economy; 5. Family relationships; 6. Wider kin; 7. Starting work; 8. Jobs; 9. Apprenticeship; 10. Schooling; 11. Conclusion; Bibliography.
Bibliografische referenties ; index
Keywords: Child labor -- History. -- Great Britain; Childhood -- History. -- Great Britain; Industrial revolution -- Great Britain